Fasting in Ramadan of Muslim patients with diabetes Mellitus, and knowledge and practice in relation to diabetes control in Brunei. (October 2018) - Tan, Caroline; Yong, Alice M.L.; Haji Mohamad, Mohamad Azmi; Abdul Rahman, Hanif; Naing, Lin
Highlights: First epidemiologic report of fasting by people with diabetes in Brunei. Prevalence of Ramadan fasting was 93.4% with 24.1 average number of fasting days. 49.1% consulted healthcare professionals prior to fasting. 38.1% monitored blood glucose levels throughout fasting month. Abstract: Aim: To investigate the fasting pattern of patients with Diabetes Mellitus in Brunei Darussalam, specifically, their fasting activities, and knowledge and practice in relation to diabetes control during fasting in Ramadan. Methods: Cross-sectional study that included 18 years and older, Muslim patients with diabetes Mellitus who attended the main Diabetes Centre in Brunei. A self-administered questionnaire was designed, tested and used to collect the demographic information, fasting duration, knowledge and practice on diabetes control during fasting, and reasons of fasting as a Muslim. Results: 183 participants with a mean age of 53.7 (SD 11.52) years were recruited. Prevalence of fasting during Ramadan was 93.4% with an average number of days of fasting was 24.1 days. Those with age 55 and above had significant higher prevalence of fasting than the younger group ( p  = 0.010). Only 49.1% of participants had consulted their healthcare professionals of their intentions to fast prior to the Ramadan, and only 38.1% of participants monitored blood glucose levels throughout the month. Conclusions: Diabetes education and early treatment adjustment especially before and during the month of Ramadan is essential to minimize hypoglycaemic risks and frequency of diabetes complications.